Implementation of PBL Model on Strengthening Students' Numerical Literacy and Digital Literacy Skills - Samuel Juliardi Sinaga; Najamuddin Najamuddin; Dinie Anggreani Dewi; Urip Widodo; Kevin William Andri Siahaan; Misbah Misbah; Ghufran Hasyim Achmad; Froilan D Mobo (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to look at the effectiveness of project-based learning on literacy skills and digital literacy of students in elementary schools. This study used a quantitative approach with the control group research method and the pretest-posttest research design. The students used in this study were grade II elementary school students with a selected population of 5 classes consisting of 120 students, randomly selected to meet the control class consisting of 20 students and 1 experimental class in each class who realized that the ability to understand numerical concepts and arithmetic operational skills in everyday life is not in accordance with numerical literacy indicators. The overall results described in the Manova test (Multivariate Analysis of Variance) show that the project-based learning model has proven effective in increasing students' digital literacy and numerical literacy skills. This can be seen from the results of the experimental class using the Project Based Learning model which is superior to the control class using the traditional learning model. Based on the results of the analysis and discussion, it can be concluded that the Project Based Learning model is effectively used to improve the numerical literacy skills and digital literacy of second grade elementary school students. So that through this research students can achieve the expected indicators in the application of numeracy and digital literacy.